The Impact of Strategic Leadership Practices on Entrepreneurial Orientation “A Comparative study between the Khanyounis Training College and College of Intermediate Studies at the University of Palestine - Gaza Strip” - Ahmed, Adham Ibrahim Mohammed; Khojaly, Musa Ahmed Adam (Journal of Economic, Administrative and Legal Sciences, 2021)
This study aimed to identify the impact of strategic leadership practices and their role in enhancing the entrepreneurial orientation. It was based on knowing the impact of strategic leadership practices (defining strategic direction, investing human capital, supporting organizational culture, emphasizing ethical practices, implementing balanced control) on enhancing the entrepreneurial orientation (proactive measures, risk taking, creativity, independency, competitive aggressiveness) among employees of the Khan Yunis Training College and the College of Intermediate Studies at the University of Palestine in the Gaza Strip. As well as revealing the differences between the average estimates for the variables: (gender, age, job title, number of years of service, academic qualification), and making future recommendations. Descriptive and analytical approaches were used as they made use of the historical method. All items were selected according to the comprehensive survey methodology, and the questionnaire was designed as a study tool to collect data. The study population consisted of workers (administrators and academics) in the Khan Yunis Training College and the College of Intermediate Studies at the University of Palestine. It reached (124) participants, and (110) questionnaires were retrieved. The hypotheses of the study were represented by the hypothesis that there is a statistically significant relationship between strategic leadership practices and strengthening the entrepreneurial orientation of the employees of the Khan Yunis Training College and the College of Intermediate Studies at the University of Palestine in the Gaza Strip. (Defining strategic direction, investing human capital, supporting organizational culture, emphasizing ethical practices, implementing balanced control) and (proactive measures, risk taking, creativity, independency, competitive aggressiveness) among the participants. The findings of this study show that there is a positive impact between (Defining strategic direction, investing human capital, supporting organizational culture, emphasizing ethical practices, implementing balanced control) and (proactive measures, risk taking, creativity, independency, competitive aggressiveness). There is a statistically significant impact relationship between the averages of respondents’ responses to strategic leadership practices and the variables (gender, age, job title, number of years of service, academic qualification) in proportions that are high in nature and positive and direct in their direction between the two variables. Varying, there is a statistically significant impact relationship between the averages of the respondents’ responses on enhancing the entrepreneurial orientation of the employees of the Khan Yunis Training College and the College of Intermediate Studies at the University of Palestine and between the variables (gender, age, job title, number of years of service, academic qualification) in varying proportions. The study recommended work to improve strategic leadership practices in its various dimensions and to work on educating university administrations about the importance of building an entrepreneurial orientation and establishing a unit in every college / university concerned with leadership to contribute permanently to building a successful entrepreneurial trend and enhance the culture of the entrepreneurial employee and work to offer rewards for the proactive workers and pay attention to different leadership styles and practice. Especially those related to strategic leadership in educational institutions.